Inspired by nature: Fiber networks functionalized with tannic acid and condensed tannin-rich extracts of Norway spruce bark show antimicrobial efficacy - Jyske, Tuula; Liimatainen, Jaana; Tienaho, Jenni; Brännström, Hanna; Aoki, Dan; Kuroda, Katsushi; Reshamwala, Dhanik; Kunnas, Susan; Halmemies, Eelis; Nakayama, Eiko; Kilpeläinen, Petri; Ora, Ari; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
This study demonstrated the antibacterial and antiviral potential of condensed tannins and tannic acid when incorporated into fiber networks tested for functional material purposes. Condensed tannins were extracted from industrial bark of Norway spruce by using pressurized hot water extraction (PHWE), followed by purification of extracts by using XADHP7 treatment to obtain sugar-free extract. The chemical composition of the extracts was analyzed by using HPLC, GC‒MS and UHPLC after thiolytic degradation. The test matrices, i.e., lignocellulosic handsheets, were produced and impregnated with tannin-rich extracts, and tannic acid was used as a commercial reference. The antibacterial and antiviral efficacy of the handsheets were analyzed by using bioluminescent bacterial strains (Staphylococcus aureus RN4220+pAT19 and Escherichia coli K12+pCGLS11) and Enterovirus coxsackievirus B3. Potential bonding of the tannin-rich extract and tannic acid within the fiber matrices was studied by using FTIR-ATR spectroscopy. The deposition characteristics (distribution and accumulation patterns) of tannin compounds and extracts within fiber networks were measured and visualized by direct chemical mapping using time-of-flight secondary ion mass spectrometry (ToF-SIMS) and digital microscopy. Our results demonstrated for the first time, how tannin-rich extracts obtained from spruce bark side streams with green chemistry possess antiviral and antibacterial properties when immobilized into fiber matrices to create substitutes for plastic hygienic products, personal protection materials such as surgical face masks, or food packaging materials to prolong the shelf life of foodstuffs and prevent the spread of infections. However, more research is needed to further develop this proof-of-concept to ensure stable chemical bonding in product prototypes with specific chemistry.